Faktor-Faktor Yang Mempengaruhi Pendapatan Tenaga Kerja Wanita di Swalayan (Studi Kasus Kecamatan Banjarmasin Utara) - Saputra , Prambudi Kiki (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The purpose of this study is to obtain the answers stated above to see whether the education level factor, the number of dependents under five, and age have a significant effect on the income of female laborers in supermarkets in North Banjarmasin District. The data analysis method used is descriptive. Based on the study results, it can be concluded that the influence of the level of education, the number of dependents of toddlers, and age on the income of female workers in supermarkets in North Banjarmasin District.